AN INVESTIGATION OF STUDENTS’ MASTERY OF ENGLISH VOCABULARY AT INDONESIA EDUCATION STUDY PROGRAM IN STKIP PGRI LUBUKLINGGAU - Triyogo, Agus; Syaprizal, Syaprizal (Universitas Lambung Mangkurat, 2019)
the aimed of this research was to describe how many word students able wrote English vocabulary in short time and to describe the students’ difficulties in mastery English vocabulary. This research designed in qualitative descriptive method, the data collected through written test and unstructured interview by using Focus Group Discussion. The subject of this research was twenty students grade two of Bahasa Indonesia Study Program at STKIP PGRI Lubuklinggau. The results showed: in the writing English vocabulary test in three type Noun, verb and Adjective, students able to wrote avarage10 word in each part and the students’ difficulties such as: Students seldom reading English text so their vocabulary mastery very low, Students has low ability to remember new English word caused of never practiced in the daily life and students confuse in using irregular word in arrange the sentence both writing and speaking.